Pharmacognostical and analytical studies of leaves of Cardiospermum canescens Wall - G. Penchala Pratap,; G. Sudarsanam,; B. Jyothi,; G.P.Prasad,; N.M.A.Rasheed, (International Journal of Phytomedicine, 2012)
The present investigation deals with the Microscopical, physicochemical and preliminary phytochemical studies on the leaves of Cardiospermum canescens Wall. with the scope of Ethnic importance. Leaves of this plant are used by the tribes of Nellore district as a single drug remedy to treat for Dysentery and Rheumatoid arthritis. In the present work the leaf of the plant was subjected to various microscopical and physico- preliminary phyto chemical evaluations. In the microscopical studies, the different cell structures and arrangements were studied. Physicochemical parameters like loss on drying, total ash value, acid insoluble ash, water insoluble ash, various extractive values etc., were carried out. Further, qualitative tests for various functional groups like Triterpenoids, alkaloids, glycosides etc..., were carried out and HPTLC profile was also established with Methanolic extract.